The Economics of Salafi Feminism: Portrait of Social Construction and Entrepreneurship of Salafi Women in Lampung Indonesia - Tobibatussaadah Tobibatussaadah; Dharma Setyawan; Dwi Nugroho (State Institute of Islamic Studies (IAIN) Salatiga, 2021)
This study intends to reveal the economy of Salafi feminism, social construction, and entrepreneurship of Salafi women in the cities of Metro, Central Lampung, and East Lampung. Salafi women are a cultural variant of Muslim society that claims to be puritanical on ideology. They embrace Islam using syar`i mean and are strongly committed to realizing noble and religious goals. In these complex rules of life, they follow the Prophet`s sunnah, namely trading. In terms of the association of Salafi women in public, it does not prevent them from carrying out entrepreneurial movements. The Salafi women's movement in trade is interesting to study. This study uses a phenomenological approach using Berger's theory, namely the social construction of reality. This research reveals that apart from women who are Salafi qanaah for every provision of their husbands, they also carry out economic activities. In these activities, they continue to practice every religious norm, recommended by scholars as salaf ash Salih, and prioritize permission from husbands and parents.